2016
DOI: 10.1371/journal.pone.0157090
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and the Default Mode Network in Children with Sickle Cell Disease: A Resting State Functional MRI Study

Abstract: Cerebrovascular complications are frequent events in children with sickle cell disease, yet routinely used techniques such as Transcranial Doppler (TCD), Magnetic Resonance (MRI) and Angiography (MRA), insufficiently explain the cause of poor cognitive performances. Forty children with SS-Sβ° (mean age 8 years) underwent neurocognitive evaluation and comprehensive brain imaging assessment with TCD, MRI, MRA, Resting State (RS) Functional MRI with evaluation of the Default Mode Network (DMN). Sixteen healthy ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…The 2 previously published pediatric studies differed in study design and technique, with Colombatti et al reporting increased connectivity within regions of the DMN with resting-state fcMRI and Sun et al reporting attenuated activation and deactivation in regions of the DMN in SCD with task-based fcMRI. 18,21 These 2 investigations were limited by a high prevalence of vasculopathy within the SCD cohort 18 and smaller sample size. 21 Although it has been shown that the hemodynamic response function (HRF) does not differ in patients with SCD compared with controls, 19 it remains unclear if the presence of vasculopathy affects the HRF, potentially impacting the interpretation of functional connectivity results in SCD cohorts that include participants with vasculopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 previously published pediatric studies differed in study design and technique, with Colombatti et al reporting increased connectivity within regions of the DMN with resting-state fcMRI and Sun et al reporting attenuated activation and deactivation in regions of the DMN in SCD with task-based fcMRI. 18,21 These 2 investigations were limited by a high prevalence of vasculopathy within the SCD cohort 18 and smaller sample size. 21 Although it has been shown that the hemodynamic response function (HRF) does not differ in patients with SCD compared with controls, 19 it remains unclear if the presence of vasculopathy affects the HRF, potentially impacting the interpretation of functional connectivity results in SCD cohorts that include participants with vasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The disparate results of prior investigations into the impact of SCD on fcMRI are challenging to interpret due to the heterogeneity in study design and approach. [17][18][19][20][21][22][23][24] We aim to further our understanding of the pathophysiology of the cognitive complications of SCD using robust statistical analyses of fcMRI data, including homotopy (a global metric assessing the connectivity between the left and right hemispheres) 25 and large-scale networks specific to different neurocognitive functions. Using MRI to measure OEF and functional connectivity in a single session, we prospectively enrolled children with SCD and healthy controls to test our hypothesis that children with SCD would have decreased functional connectivity, and that children experiencing the greatest metabolic stress, as measured by OEF, would have disrupted functional network connectivity.…”
mentioning
confidence: 99%
“…Brain imaging studies (Balci et al, 2012; Chen et al, 2017; Schatz and Buzan, 2006; Scott Mackin et al, 2014) have shown atrophy of the corpus collosum, frontal lobes, thalamus, and basal ganglia, in addition to increased resting-state functional connectivity (RS-FC) of the default-mode network (DMN) in children, that was associated with cognitive decline (Chen et al, 2017; Colombatti et al, 2016; Schatz and Buzan, 2006; Scott Mackin et al, 2014). Increased amplitude of low-frequency fluctuations (ALFF) in the orbitofrontal cortex, anterior cingulate cortex (ACC) and posterior cingulate (PCC) compared to anemic controls has also been observed (Coloigner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…from sleep apnea, acute anemia) especially in light of diminished autoregulatory cerebrovascular flow reserve due to basal hyperemia [ 33 , 34 ]. Repeated ischemia-reperfusion injury may be responsible for decreased activity in watershed cortical areas [ 61 ]. Interestingly, we observed comparable loss of white matter in the ACTL group and SCD patients in the anterior and middle cerebral artery territories, consistent with chronic intermittent hypoxia in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lower gyral white matter in watershed regions was previously reported in a study of SCD patients which may be indicative of preclinical white matter injury [ 12 ]. In [ 61 ], control temporal-concatenation group ICA analysis was not able to detect connectivity differences among SCD patients according to WMH volume. Contrary to this result, decreased ALFF was observed in small areas in the frontal pole and mSFG between patients with and without silent stroke.…”
Section: Discussionmentioning
confidence: 99%